A prospective randomized controlled trial comparing laparoscopic versus open Whipple’s procedure for periampullary malignancy - Bhingare, Pravin; Wankhade, Sunil; Gupta, Brajesh B.; Dakhore, Sanjay (International Surgery Journal, 2019)
Background: Laparoscopic surgery in cases of periampullary region malignancies has been emerging as a preferable alternative to open pancreatoduodenectomy due to their benefits such as early mobilization and shorter duration of hospital stay. We conducted this study to determine whether laparoscopic approach is comparable to open pancreatoduodenectomy in terms of hospital stay, blood loss, complications, pathological radicality with oncological safety and overall postoperative short-term outcomes. Methods: This was a single-center, non-stratified, balanced allocation, open-label, parallel-group randomized control study in which patients who had undergone Whipple’s procedure were included. Patients were randomized after confirmation of non-metastatic status into either the laparoscopy (N=15) or open surgery group (N=15). The primary outcome variable was duration of postoperative hospital stays. Secondary outcomes were duration of surgery, blood loss, complication rates (using definitions of the international study group of pancreatic surgery) and pathological radicality of resection. Results: Pain in abdomen was the predominant complaint which was seen in 12 (80%) and 10 (66%) patients each. The other common symptoms were weight loss, vomiting and jaundice. Surgical site infection, mean blood loss and mean operative duration was significantly lower in laparoscopic group (P<0.05). Mean tumor size was more in open group. Mortality was comparable in both the groups. Conclusions: Laparoscopic pancreatoduodenectomy offers significant benefit in terms of hospital stay, surgical site infection, mean blood loss, mean operative duration and mean interval of duration receiving chemo/radiotherapy as compared to open surgery in cases of periampullary region malignancy.